Did My Hand Move in a Mirror? Body Ownership Induced by the Mirror Hand Illusion - Iida, Akihiro; Saito, Hidekazu; Ota, Hisaaki (Frontiers in Human Neuroscience, 2021)
Although the illusion that the mirror image of a hand or limb could be recognized as a part of one’s body behind the mirror, the effect of adding tactile stimulation to this illusion remains unknown. We, therefore, examined how the timing of tactile stimulation affects the induction of body ownership on the mirror image. Twenty-one healthy, right-handed participants (mean age = 23.0 ± 1.0 years, no medical history of neurological and/or psychiatric disorders) were enrolled and a crossover design was adopted in this study. Participants’ right and left hands were placed on the front and back sides of the mirror, respectively, then they were asked to keep looking at their right hand in the mirror. All participants experienced two experiments; one was with tactile stimulation that was synchronized with the movement of a mirror image (synchronous condition), and the other one was with tactile stimulation that was not synchronized (asynchronous condition). The qualitative degree of body ownership for the mirrored hand was evaluated by a questionnaire. Proprioceptive drift (PD), an illusory shift of the felt position of the real hand toward the mirrored hand was used for quantitative evaluation of body ownership and measured at “baseline,” “immediately after stimulation,” “2 min after stimulation,” and “4 min after stimulation.” The results of the questionnaire revealed that some items of body ownership rating were higher in the synchronous condition than in the asynchronous condition (p < 0.05). We found that PD occurred from immediately after to 4 min after stimulation in both conditions (p < 0.01) and there was no difference in the results between the conditions. From the dissociation of these results, we interpreted that body ownership could be elicited by different mechanisms depending on the task demand. Our results may contribute to the understanding of the multisensory integration mechanism of visual and tactile stimulation during mirror illusion induction.